The Effect of Therapeutic Exercises of Degree and Severity of Tear Tendon Muscle Tendon Rupture and Some Physical and Functional Variables for Athletes - Ahmed Atshan Abdulradha (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research problem included in the injury of the rotator cuff tendon rupture and the study aimed at - thenumber of therapeutic exercises severely and the degree of injury to qualify for the injury of the rotator cufftendon rupture and some physical and functional variables for athletes - knowledge of the effect of therapeuticexercises severely and the degree of injury to qualify for injury to the rotator cuff tendon rupture and somevariables.As for the research method, the researcher used the experimental method and by designing theexperimental group with one pre-measured, middle, and dimensional measurement for its suitability and thenature of the problem.